2020
DOI: 10.1534/genetics.120.303333
|View full text |Cite
|
Sign up to set email alerts
|

Spontaneous Polyploids and Antimutators Compete During the Evolution of Saccharomyces cerevisiae Mutator Cells

Abstract: Heterozygous mutations affecting DNA polymerase (Pol) exonuclease domains and homozygous inactivation of mismatch repair (MMR) each generate "mutator" phenotypes capable of driving tumorigenesis. Cancers with both defects exhibit an explosive increase in mutation burden that appears to reach a threshold, consistent with selection acting against further mutation accumulation. In haploid yeast, simultaneous defects in polymerase proofreading and MMR select for "antimutator" mutants that suppress the mutator phen… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 57 publications
2
7
0
Order By: Relevance
“…Indeed, when we analysed the prevalence of mutations in POL2 we found evidence of additional mutations in this gene often co-occurring with the stronger mutators (P301R, M459K, S312F, L439V) but only rarely with the weaker mutators or in wild-type cells ( Supplementary Figure S3A and B ). In line with recent findings ( 33 ) we also identified one spontaneous diploidization event in four isolates of the pol2-M459K haploid strain, which co-occurred with several additional pol2 mutations ( Supplementary Figure S3A, B; Figure S5C , blue circle).…”
Section: Resultssupporting
confidence: 92%
See 3 more Smart Citations
“…Indeed, when we analysed the prevalence of mutations in POL2 we found evidence of additional mutations in this gene often co-occurring with the stronger mutators (P301R, M459K, S312F, L439V) but only rarely with the weaker mutators or in wild-type cells ( Supplementary Figure S3A and B ). In line with recent findings ( 33 ) we also identified one spontaneous diploidization event in four isolates of the pol2-M459K haploid strain, which co-occurred with several additional pol2 mutations ( Supplementary Figure S3A, B; Figure S5C , blue circle).…”
Section: Resultssupporting
confidence: 92%
“…As previously observed for several other DNA polymerase mutator alleles ( 16 , 24 , 32 ), sporulation of most pol2-ultra msh2Δ heterozygous diploids did not yield viable double mutant strains for the strongest ultra -mutators ( pol2-P301R , pol2-M459K and pol2-S312F ). Microscopic observation of these spores revealed that they germinated to vegetative cells but ceased to divide after a few generations, a phenotype consistent with extreme mutational burden leading to ‘error-induced extinction’ ( 32 , 33 ). By contrast, double mutants for the hypermutator pol2–4 in combination with msh2Δ were obtained from corresponding heterozygous diploids but displayed reduced colony size compared to MMR-proficient controls.…”
Section: Resultsmentioning
confidence: 97%
See 2 more Smart Citations
“…To compare the mutation spectra between strains, mutations were first classified as one of the 6 general classes of base-substitutions (A>C, A>G, A>T, C>A, C>G, C>T) or as single base-pair insertions or deletions. We then compared the mutation spectra of the two control strains LCTL1 and LCTL2 to all other haploid isolates as well as one spectrum published by Lang et al (2008) (a total of 35 tests) using a pairwise hypergeometric test (Adams and Skopek, 1987), a custom python script (Tracy et al ., 2020). In the first round of this test, the paired mutation counts were arranged in a 2 x 8 contingency table.…”
Section: Methodsmentioning
confidence: 99%